Protein profiles of nasal lavage fluid from individuals with work‐related upper airway symptoms associated with moldy and damp buildings. (9th November 2015) - Wåhlén, K.; Fornander, L.; Olausson, P.; Ydreborg, K.; Flodin, U.; Graff, P.; Lindahl, M.; Ghafouri, B.
Abstract: Upper airway irritation is common among individuals working in moldy and damp buildings. The aim of this study was to investigate effects on the protein composition of the nasal lining fluid. The prevalence of symptoms in relation to work environment was examined in 37 individuals working in two damp buildings. Microbial growth was confirmed in one of the buildings. Nasal lavage fluid was collected from 29 of the exposed subjects and 13 controls, not working in a damp building. Protein profiles were investigated with a proteomic approach and evaluated by multivariate statistical models. Subjects from both workplaces reported upper airway and ocular symptoms. Based on protein profiles, symptomatic subjects in the two workplaces were discriminated from each other and separated from healthy controls. The groups differed in proteins involved in inflammation and host defense. Measurements of innate immunity proteins showed a significant increase in protein S100‐A8 and decrease in SPLUNC1 in subjects from one workplace, while alpha‐1‐antitrypsin was elevated in subjects from the other workplace, compared with healthy controls. The results show that protein profiles in nasal lavage fluid can be used to monitor airway mucosal effects in personnel working in damp buildings and indicate that the profile may be separated when the dampness is associated with the presence of molds.